Variation in oil content and fatty acid profiles of peanut cultivars across three mediterranean locations (Bangladesh Journal of Botany, 2025)
The fatty acid profile of peanut oil is an important factor that affects the quality of peanut seeds and its products. Oil content and fatty acid composition vary significantly depending on cultivar and growing location.The analysis of variance revealed that the varieties differed in all traits examined in the study, that the locations had significant effects on fatty acids other than stearic, eicosenoic, and arachidic acids, and that their interactions were significant for all traits examined. Halisbey variety had the highest oil content and theBrantley variety, which is a high oleic variety, had the highest oleic acid, O/L percentage, and lowest linoleic acid and iodine value, while the Flower-22 variety had the highest linoleic acid and iodine value and the lowest oleic acid and O/L ratio.Bangladesh J. Bot. 54(4): 977-986, 2025 (December)